Association between individual, work-related and organizational factors and adherence to standard precautions - Quézia Boeira da Cunha; Etiane de Oliveira Freitas; Tânia Solange Bosi de Souza Magnago; Maria Meimei Brevidelli; Mariana Pellegrini Cesar; Silviamar Camponogara
ABSTRACT Objective: To verify the association between individual, work-related and organizational factors with adherence to standard precautions. Method: Cross-sectional study, carried out from January to June 2016 with 602 nursing workers from a university hospital. Ten Likert-type psychometric scales were used, with 57 items, organized in three domains: individual, work-related and organizational factors. Data were analyzed with descriptive and inferential statistics. Results: The adherence to the standard precautions obtained a mean intermediate score (4.30 ± 1.03) and a positive correlation with the Risk Personality Scales (r = 0.136, p <0.0001), Prevention Efficacy (r = 0.109 , p <0.0001), Obstacles to follow the precautions (r = 0.394, p <0.0001), PPE availability (r = 0.189 p <0.0001), Safety Climate (r = 0.325, p <0 , 0001) and Training on Prevention of Occupational Exposure (r = + 0.308, p <0.0001). Conclusion: Adherence to standard precautions is associated with individual, work-related, and organizational factors.